solve dy/dx = (y^2)(e^2y), y(0) = 1. e^2y = x lnx = 2y. lnx/2 = y dy/y^2 = (0.5)(lnx)dx -y^-1 = (.5)(xlnx-x) + C C = -1 y = -2/(xlnx -x -1) Is this correct? Im stuck here since lnx is not determinable.
Follow Math Help Forum on Facebook and Google+
Originally Posted by lord12 solve dy/dx = (y^2)(e^2y), y(0) = 1. e^2y = x lnx = 2y. lnx/2 = y dy/y^2 = (0.5)(lnx)dx -y^-1 = (.5)(xlnx-x) + C C = -1 y = -2/(xlnx -x -1) Is this correct? Im stuck here since lnx is not determinable. . How did you get ? According to your substitution, .
first, where does this come from? or is it included in the given?
View Tag Cloud